Penyuluhan Dan Cek Kesehatan Di Puskesmas Delinom Kel.Muara Dua Kec.Prabumulih Timur Kota Prabumulih - Pusphita, Riri; Wilidiawati, Sri; Armarena, Armarena; Fitriani, Lusi; Mailani, Eka; Salistyawati, Nichi; Ardina, Risa; Yanti, Yenny Nopi; Rustandi, Handi; Rohani, Tuti; Azissah, Danur (Universitas Dehasen Bengkulu, 2025)
Hypertension or high blood pressure is a major global health problem that occurs in all regions around the world. Approximately 31.1% of the world's adult population lives with hypertension, with 28.5% in high-income countries and 31.5% in low- and middle-income countries. Adrenaline increases the blood pressure that flows due to arterial contraction (vasoconstriction) resulting in an increase in heart rate, a person experiencing stress continues, blood pressure will remain high so that this person can be called hypertensive. Hypertension is the biggest cause of stroke, both systolic and diastolic blood pressure. Hypertension is called the silent disease because people do not know they have hypertension until they have their blood pressure checked. WHO (Word health organisation) states that hypertension is a condition where blood vessels have high blood pressure (systolic blood pressure ≤ 140 mmhg or diastolic blood pressure ≤ 90 mmhg). This counselling activity aims to increase the level of knowledge of the community, especially mothers related to hypertension, and to see a picture of the health status of mothers in RW 02 RT 03 Kel. Muara dua Kec.Prabumulih Timur. The place of this education and health check activity was carried out at RW 02 RT 03 Kel. Muara dua Kec.Prabumulih Timur. The time used was 13 January 2025 to 23 January 2025 consisting of 38 people who could participate in this education and health check activity. The counselling method used in this study was discussion and question and answer. Overall, this education and health check activity has had a positive impact on the community of RW 02 RT 03 Kel. Muara dua Kec.Prabumulih Timur. Increased awareness of the importance of early detection and control of hypertension is expected to reduce the risk of more serious complications in the future. The success of this programme also proves that collaboration between students, health workers and the community is very important in an effort to improve the health status of the community.